Innovation in Librarianship: a bibliometric analysis of the scientific production in Scopus (2004-2023) - Murillo-González, Adrián (2025)
The aim of this research is to provide an updated status of publications on innovation in librarianship, using the SCOPUS database as the main source of information. The methodology adopted is quantitative with a descriptive approach, analyzing documents published between 2004 and 2023 that mention key terms related to innovation and librarianship. Among the main findings, the diversity in journal impact, measured by the SJR index, stands out, indicating significant variations in quality and prestige. Research trends were also identified, such as the integration of emerging technologies (artificial intelligence and augmented reality) and the adoption of new management models and personalized services. The conclusions point out that international cooperation in library research is crucial, as it allows for the exchange of ideas and best practices, thus enriching the quality and impact of research. Furthermore, it is highlighted that libraries that adopt innovative approaches not only optimize their operations, but also reinforce their relevance as centers of learning, information and culture. It is suggested that future research should focus on exploring new ways of integrating emerging technologies into library management and services.